Revitalizing the Lampung language through illustrated conversation books: A sociolinguistic approach - Reza Pustika; Nufikha Ulfah; Padika Arbi Ragawilapa; Susi Susyanti; Fellanisa Priyono Putri; Severinus Sakaria (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
The Lampung language is currently facing a decline in daily use among younger generations, raising concerns about its potential endangerment. This study investigates the role of illustrated conversation books as a pedagogical tool to support the revitalisation of the Lampung language, using a sociolinguistic approach that considers learners’ perceptions, motivation, and attitudes toward language preservation. Data were collected through a questionnaire distributed to 102 respondents, with items grouped into three aspects: perceptions of book design, motivation to learn Lampung, and attitudes toward language preservation. The findings indicate that 82.4%–84.3% of respondents agreed that illustrations and attractive visual design improved comprehension, engagement, and enjoyment in learning. Motivation-related responses were moderately positive (67.6%–70.6%), with students expressing pride in learning Lampung but showing a need for broader reinforcement from cultural and social contexts. Attitudes toward preservation were strongly positive, with 91.1% agreeing that illustrated books can be an effective strategy for safeguarding the language, although only 55.9% expressed willingness to teach it to others. These results align with multimedia learning theories and sociolinguistic perspectives on language revitalisation, highlighting the importance of visual pedagogical resources while underscoring the need for community and institutional support. The study concludes that illustrated conversation books can serve as effective entry points for revitalising the Lampung language. The illustrated conversation books serve as a new pedagogical tool for teaching and preserving the Lampung language. This book can also provide a fresh assessment of students’ perceptions, motivation, and attitudes toward learning in Lampung.